Plataforma de producción agroindustrial para la región central (2019)
Sesquilé is a municipality of Cundinamarca in the province of Almeidas with a strategic location, its degree of connectivity with the proximity to the capital of Bogotá and with the north highway towards Tunja and with the concession of the eastern perimeter and 4th generation towards Villavicencio; with participating municipalities such as Suesca, Chocontá, Nemocón, Guatavita and Gachancipá, all with great potential that through hierarchies we notice the presence of a municipality that has the ability to react positively to a competitiveness plan where the provinces are participants in the economy of a country, achieving productive activities and the use of resources and impacting the territory. The central region has a great agro-industrial potential and environmental strength that links all municipalities to the capital, a series of studies is carried out to approximate the needs of the region and the transmission of a solution to these problems, with this it is carried out a Master Plan proposal where the priority is to take advantage of this potential where the relationship with the Environment is friendly and is the consequence of actions that last over time.